Organized cybercrime, state crimes, and cyberterrorism - Graham, Roderick (Cybercrime and digital deviance, 2024)
This chapter introduces the reader to organized crime in the digital environment. It covers the difficulties in defining the concept and what makes Organized Crime different than “crimes that are organized.” The chapter also covers state cybercrime and cyberwar, differentiating the two phenomena by the violations they are associated with and the context in which they occur. Lastly, cyberterrorism is discussed in this chapter - a topic encircled by much speculation, but with considerably fewer examples of documented infractions. Nonetheless, the prospect of far-reaching global impact from such offending warrants proactive dialogue and safeguarding measures.